Patches of different types for carotid patch angioplasty - Orrapin, S; Benyakorn, T; Howard, DP; Siribumrungwong, B; Rerkasem, K (Cochrane Collaboration, 2021)
Background Extracranial carotid artery stenosis is the major cause of stroke, which can lead to disability and mortality. Carotid endarterectomy (CEA) with carotid patch angioplasty is the most popular technique for reducing the risk of stroke. Patch material may be made from an autologous vein, bovine pericardium, or synthetic material including polytetrafluoroethylene (PTFE), Dacron, polyurethane, and polyester. This is an update of a review that was first published in 1996 and was last updated in 2010.